Peran Ekonomi dalam Pendidikan dan Pendidikan dalam Pembangunan Ekonomi - APRIYANTI WIDIANSYAH (Cakrawala - Jurnal Humaniora, 2017)
Economic growth in Indonesia is also influenced by education. Therefore the importance of the meaning of education for economic growth in Indonesia by increasing the productivity of learning so that the successors of the nation who are still learning can better understand the science of economics and can improve the economy diindonesia that is down. With the increasing economic needs of the day, the educational factors that will help the economic growth, because with education that will produce the qualities of Human Resources (HR) is more professional both for the industrial sector and agricultural sector, and from there will impact and affect the economic growth of the nation of Indonesia in the future.